2019
DOI: 10.18178/ijiet.2019.9.5.1226
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Students Affective States through Online Learning Logs — An Application of Learning Analytics

Abstract: The affective state is determinate to online learning quality. It is related to students' attitude, learning motivation, and learning engagement. Learning affective states consists of engagement, frustration, confusion, and off-task state in this study. Different affective states are associated with different online learning behavior features. Affective states analysis consists of data collecting, data processing, affective states analyzing, evaluating, and intervening. Students' affective states can be analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For instance, Đurđević Babić (2015) reported that neural network model with an accuracy score of 73.33% is the best model for predicting students’ satisfaction in a course using their learning data. Wang et al (2019) revealed that students’ learning affective states such as concentration, frustration, confusion, and off-task could be predicted from their learning data with F-scores of 57%, 74%, 44%, and 75% respectively using Nave Bayes and K* algorithms. Moreover, Park et al (2016) applied multimodal models and predicted the persuasiveness of communication modalities on social multimedia with a mean accuracy score of 70.34%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Đurđević Babić (2015) reported that neural network model with an accuracy score of 73.33% is the best model for predicting students’ satisfaction in a course using their learning data. Wang et al (2019) revealed that students’ learning affective states such as concentration, frustration, confusion, and off-task could be predicted from their learning data with F-scores of 57%, 74%, 44%, and 75% respectively using Nave Bayes and K* algorithms. Moreover, Park et al (2016) applied multimodal models and predicted the persuasiveness of communication modalities on social multimedia with a mean accuracy score of 70.34%.…”
Section: Discussionmentioning
confidence: 99%
“…The neural network model known as the multilayer perceptron achieved the best overall classification accuracy with an average of 73.33%. Moreover, a study showed that learning log data of students could be utilized to build models for detecting various learning affective states (such as engagement, frustration, confusion, and off-task) of students (Wang et al, 2019). The study results indicated that the correlation between affective state analysis and self-report was 83.6%, demonstrating the validity of the data analysis model.…”
Section: Related Workmentioning
confidence: 99%
“…The term “affective states of students in learning” has been used to denote a range of variables related to their motivation, engagement, and attitude. For example, in Wang et al ( 2019 ), the affective states comprise confusion, engagement, off-task, and frustration. According to Shute and Zapata-Rivera ( 2012 ), the affective states consist of motivated, attentive, engaged, and frustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting positive and negative affective states of students is important in improving and supporting their learning processes and progress. According to research, learning affective states include students' concentration, confusion, frustration and off-task behaviors (Wang et al, 2019 ). A number of studies conducted in the area of affective computing in education have recognized the role of affective states especially the learning affective states in facilitating learning activities (Wiggins et al, 2015 ; Jiménez et al, 2018 ; Standen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation